SISTEM INFORMASI EDUKASI PENCEGAHAN COVID-19 PADA ANAK USIA DINI MENGGUNAKAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE BERBASIS ANDROID - Nur Mustika; Kamaruddin Kamaruddin; Pujianti Wahyuningsih (LPPM Poltek ST Paul, 2021)
The importance of understanding the Covid-19 disease in early childhood has become an important concern by the government and the Indonesian people. The purpose of this study is to build an Android-based educational information system for the prevention of Covid-19 disease in early childhood. The problem faced by the community is that it is difficult to provide understanding to children to comply with health protocols from the government. The method used to build an educational information system application uses the multimedia development life cycle (MDLC) method. The MDLC method consists of 6 stages used in this study, namely concept, design, material collection, manufacture, testing and distribution. The result of this research is to build a covid-19 prevention education information system, where this application provides understanding to early childhood and provides information to children in the form of applications in the form of multimedia that can be accessed via Android-based smartphones.